2022
DOI: 10.1021/acs.jafc.2c01667
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stage Blue-Light-Guided Membrane and DNA-Targeted Photodynamic Inactivation Using Octyl Gallate for Ultraefficient Eradication of Planktonic Bacteria and Sessile Biofilms

Abstract: This study aimed to investigate the synergistic bactericidal activity and mechanism of dual-stage light-guided membrane and DNA-targeted photodynamic inactivation (PDI) by the combination of blue light (BL, 420 nm) and the food additive octyl gallate (OG) against Vibrio parahaemolyticus in planktonic and biofilm growth modes. While OG serves as an outstanding exogenous photosensitizer, the planktonic cells were not visibly detectable after the OG-mediated PDI treatment with 0.2 mM OG within 15 min (191.7 J/cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 46 publications
(133 reference statements)
1
16
0
Order By: Relevance
“…Shi et al [ 52 ] investigated the bactericidal and antibiofilm effects of photodynamic inactivation (PDI) against the foodborne pathogen Vibrio parahaemolyticus using the combined action of OG, a food additive, and the application of BL. PDI was used on the pathogen, in both planktonic and biofilm growth forms, to target cell membranes and DNA.…”
Section: Octyl Gallatementioning
confidence: 99%
“…Shi et al [ 52 ] investigated the bactericidal and antibiofilm effects of photodynamic inactivation (PDI) against the foodborne pathogen Vibrio parahaemolyticus using the combined action of OG, a food additive, and the application of BL. PDI was used on the pathogen, in both planktonic and biofilm growth forms, to target cell membranes and DNA.…”
Section: Octyl Gallatementioning
confidence: 99%
“…To observe the three-dimensional (3D) structure of biofilms, samples were collected by confocal laser scanning microscopy (CLSM) (Leica TCS SP8 Scan Head, Germany) with the LIVE/ DEAD Backlight Bacterial Viability Kits (Molecular Probes, Invitrogen, USA). 10 2.5. Eradication of the Mature Biofilm.…”
Section: Pdi Of Planktonic Bacteriamentioning
confidence: 99%
“…Our previous studies demonstrated that OG could insert into the cell membrane due to its superior affinity toward the membrane, inducing membrane rupture and cellular constituent leakage. 10 Besides, the internalized OG can further interfere with the activity of the ETC on the cytoplasmic membrane and interact with intracellular DNA with the formation of a stable complex. 20 These multitargeted modes of action between OG and biomolecules make OG exert an excellent bactericidal ability regardless of the absence or the presence of oxygen.…”
Section: Killing After Lightmentioning
confidence: 99%
See 2 more Smart Citations